(3GdPQjYIs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3ESMGb Hf eYJhb GdMhjRjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj QCjJ Cf Gedj cJGHG eJhSWG aj GdCUhd Gdabg dG jfJgj HJWhjd Edi GdEedGd hdG HGNJUGQ Edi GdENdGd Hd jchf ddMGLI SOGOG hddJHUQI RjGOG hGNJU eSGFd GdMdGa HGdGSJjaGA hGdGSJbUGA (B...s
(3BNQgG (B:s
... (3GdGSJOdGd HHQGAI Cgd GdPeI eeG jecf GdGYJeGO Ydjg dCf JYdb HGdMb HGdPeI YbdG Ch TQYG jMJGL Edi SHH GSJMbGb aEPG COi GdfXQ Edi abO SHH GdGSJMbGb Yde HQGAI GdPeI (B... (3hfMf GdBf bGWYhf cJGHfG gPG(B.s
(3ebGHdI Ydi jO cGJHgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B4/ 278s
(3GdPQjYI (B10\130s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs